The Application of a Meiocyte-Specific CRISPR/Cas9 (MSC) System and a Suicide-MSC System in Generating Inheritable and Stable Mutations in Arabidopsis - Xu, Penghui; Su, Hang; Chen, Wanli; Lu, Pingli (Frontiers in Plant Science, 2018)
The CRISPR/Cas9 system has been widely used for generating targeted mutations in various species. In Arabidopsis, it largely relies on the edited cells where the Cas9 protein performs its activity to obtain heritable and stable mutated lines. Here, we designed an improved CRISPR/Cas9 system, named as the MSC (meiocyte-specific CRISPR/Cas9) system, in which the Cas9 expression is driven by an experimentally approved meiocyte-specific promoter (AtDMC1 promoter). Two endogenous genes, including vegetative gene AtDET2 and reproductive gene AtDMC1, were targeted. We obtained heterozygous T1 plants for targeted genes with high efficiency (64%). In the T2 generation, the homozygous plants were abundant with high efficiency (37%). Analysis of Sanger sequencing results of T2 generation revealed that heritable gene mutations were high (52%). Moreover, we showed that the MSC system could sufficiently delete a middle size DNA fragment ( 500bp) between two cleavage sites with a high rate (64.15%) in the T1 plants, providing direct evidence for making complete knock-out or certain domain-depletion mutations. In addition, we further made a suicide-MSC system, which can edit the targeted endogenous gene and the exogenous Cas9 gene simultaneously, not only successfully avoiding the further destroy of alleles brought in by molecular complementary or genic allelic test, but also maintaining the stable mutated alleles for functional studies. In short, the two systems provide new approaches to generate mutations for gene functional studies.